Temperature and Vibration Monitoring System on Electric Motors From Wireless Remote Control Using Blynk App - Dwi Santoso, Agus; Eka Mahendra, Dani; Dirhamsyah, Dirhamsyah (Nusantara Publisher, 2024)
The purpose of this research is to create a device that can track the temperature and vibration of an electric motor. It has two sensors: a thermocouple sensor and a piezoelectric sensor. When the electric motor is operating, the device displays digital data in the form of numbers on the monitor screen wirelessly. This research shows that the electric motor can be effectively monitored remotely. The Blynk app can connect with the unit within 0-200 meters without any obstacles. However, if the unit is blocked by a barrier, the distance that can be covered by the Blynk application is 0-160 meters. The test results show that the average electric motor temperature measured is 31.7°C, and the percentage of error value obtained is -1.01%.